2016
DOI: 10.1371/journal.pone.0166590
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Regenerative Potential of Adipose-Derived Stem Cells Isolated from the Prominent Fat Pads in Human Lower Eyelids

Abstract: The existence of multipotent adipose-derived stem cells isolated from human orbital fat (OF) tissue has shown great therapeutic potential in tissue engineering and regenerative medicine. But the use of stem cells for therapeutic applications is influenced by their proliferative and differentiation potentials, which may be affected by the age of the donor. So far there is little knowledge about the effects of donor age on the biological properties of human orbital adipose-derived stem cells (OASCs). The intraor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 33 publications
4
29
1
1
Order By: Relevance
“…For chondrogenic or osteogenic regeneration, the spontaneous adipogenic differentiation of ADSCs should be minimized as possible. Adipogenic, chondrogenic, and osteogenic differentiation was observed in passage 3 in many studies (29)(30)(31)(32)(33)(34). The results of the present study indicated that the impact of spontaneous adipogenic differentiation reduced sufficiently after passage 3, and the cells passaged more than three times were probably suitable for chondrogenic and osteogenic regeneration.…”
Section: Discussionsupporting
confidence: 58%
“…For chondrogenic or osteogenic regeneration, the spontaneous adipogenic differentiation of ADSCs should be minimized as possible. Adipogenic, chondrogenic, and osteogenic differentiation was observed in passage 3 in many studies (29)(30)(31)(32)(33)(34). The results of the present study indicated that the impact of spontaneous adipogenic differentiation reduced sufficiently after passage 3, and the cells passaged more than three times were probably suitable for chondrogenic and osteogenic regeneration.…”
Section: Discussionsupporting
confidence: 58%
“…We also found that the synovial membranes obtained from older osteoarthritis patients contained Muse-like cells. In general, although the somatic stem cell number declines with age [17], [18], [19], our results suggest that synovial Muse-like cells may be a potential autologous cell source for cartilage regeneration and regenerative therapy in older patients. Considering that the low yield of Muse-like cells may be caused by cell damage accompanying FACS sorting, an alternative procedure for preparation of SSEA-3-positive cells may improve the yield of Muse-like cells.…”
Section: Discussionmentioning
confidence: 97%
“…Ye and collaborators compared ASCs isolated from orbital AT of old-versus-young donors, and found fewer progenitor cells, reduced proliferative rates, increased senescent features and decreased trilineage potential, despite no significant differences in overall cellular yield and immunophenotype [87]. Finally, a significant decrease in ASCs' yield and angiogenic capacity, has been demonstrated also in visceral fat depots of elder individuals [88].…”
Section: Age-related Changes In Ascs' Biology and Regenerative Propermentioning
confidence: 99%